Molecular interactions, characterization and photoactivity of Chlorophyll a/chitosan/2-HP-β-cyclodextrin composite films as functional and active surfaces for ROS production. (July 2016) - Rizzi, Vito; Fini, Paola; Fanelli, Fiorenza; Placido, Tiziana; Semeraro, Paola; Sibillano, Teresa; Fraix, Aurore; Sortino, Salvatore; Agostiano, Angela; Giannini, Cinzia; Cosma, Pinalysa
Abstract: Novel photosensitizing film based on the natural hybrid polymer Chitosan/2-hydroxy-propyl-β-Cyclodextrin (CH/CD) is synthesized introducing Chlorophyll a (CH/CD/Chl a ) as a photoactive agent for possible application in antimicrobial photodynamic therapy (PDT). The polymer absorbs visible light, in turn able to generate reactive oxygen species (ROS) and, therefore it can be used as environmental friendly and biodegradable polymeric photosensitizer (PS). The modified film is characterized by means of different spectroscopic, calorimetric, diffraction techniques and microscopic imaging methods including time-resolved absorption spectroscopy. UV–Vis, FTIR-ATR and X-ray Photoelectron Spectroscopy (XPS) analyses suggest that Chl a shows a strong affinity toward Chitosan introducing interactions with amino groups present on the polymer chains. Nanosecond laser flash photolysis technique provides evidence for the population of the excited triplet state of Chl a . Photogeneration of singlet oxygen is demonstrated by both direct detection by using infrared luminescence spectroscopy and chemical methods based on the use of suitable traps. Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM) and Differential Scanning Calorimetry (DSC) analyses confirm also the occurrence of structural changes both on the film surface and within the film layer induced by the insertion of the pigment. Moreover, X-ray Diffraction data (XRD) shows the existence of an amorphous phase for the chitosan films in all the compared conditions. Graphical abstract: Highlights: Hybrid Chitosan/2-hydroxy-propyl-β-Cyclodextrin films are synthesized. Chlorophyll a, as a photoactive agent, is introduced in the blended films. Among ROS, 1 O2 formation is confirmed by means of direct and molecular methods.